Religious Dramas in Italy. Dramaturgical Models, Thematization and Effectiveness of Biographical Miniseries - Armando Fumagalli (Ocula)
In this essay I will deal with the topic of religious miniseries for Television, that will be seen especially from the point of view of their dramatic structure. A genre that has been -and still is- extremely successful in Italy in this new century, it has had also some other products which have been a failure, at least in terms of audience. I will argue that, although many times audiences have shown to appreciate religious content, this content has to be created with a dramatic structure that conveys conflicts and emotions. I will shortly describe different dramatic models that are used, and their different outcome in terms of engagement of the audience.